Effect of hyperbaric pressure on postharvest conservation of “Palmer” mangoes - da Silva, Josiane Pereira; Inestroza-Lizardo, Carlos; Pinzetta Junior, José Sidnaldo [UNESP]; Mattiuz, Ben-Hur [UNESP] (Hindawi, 2021)
This study investigated the influence of hyperbaric pressure on the postharvest conservation of “Palmer” mango. The fruit was stored in hyperbaric chambers at 100 (control), 200, 400, 600, or 800 kPa at 22°C for 2 and 4 days. At the end of storage period, one batch of fruits was evaluated immediately and another batch kept at room condition (22°C, 51%–53% RH, at 100 kPa) for 3 days. During storage at hyperbaric pressure, there was an average 0.4% lower weight loss and 10.8% soluble solids in treatments with higher pressures (400, 600, and 800 kPa), and higher acidity preservation. Mangoes stored at 800 kPa presented a respiratory rate 22.7% lower than the control. Fruit treated at 800 kPa, at room temperature, presented lower weight loss, color maintenance, lower soluble solids, and higher titratable acidity. Hyperbaric pressure showed a positive effect on postharvest conservation of “Palmer” mango stored at 22°C. Novelty impact statement: Hyperbaric pressures at 600 and 800 kPa applied for 4 days improve the postharvest conservation of “Palmer” mangoes; Hyperbaric pressures prevented weight loss and decreased the respiratory rate at ambient temperature (22°C); The treatment at 800 kPa retarded the physicochemical processes of ripening in mangoes, confirmed by the color maintenance, the lower soluble solids, and the higher titratable acidity.